Crop diversity promotes the recovery of fungal communities in saline-alkali areas of the Western Songnen Plain - Li, Bin; Liu, Xiaoqian; Zhu, Dan; Su, Heng; Guo, Kaiwen; Sun, Guangyu; Li, Xin; Sun, Lei (Frontiers in Microbiology, 2023)
Phytoremediation is an effective strategy for saline land restoration. In the Western Songnen Plain, northeast China, soil fungal community recovery for saline phytoremediation has not been well documented among different cropping patterns. In this study, we tested how rotation, mixture, and monoculture cropping patterns impact fungal communities in saline-alkali soils to assess the variability between cropping patterns. The fungal communities of the soils of the different cropping types were determined using Illumina Miseq sequencing. Mixture and rotation promoted an increase in operational taxonomic unit (OTU) richness, and OTU richness in the mixture system decreased with increasing soil depth. A principal coordinate analysis (PCoA) showed that cropping patterns and soil depths influenced the structure of fungal communities, which may be due to the impact of soil properties. This was reflected by soil total nitrogen (TN) and electrical conductivity (EC) being the key factors driving OTU richness, while soil available potassium (AK) and total phosphorus (TP) were significantly correlated with the relative abundance of fungal dominant genus. The relative abundance of Leptosphaerulina, Alternaria, Myrothecium, Gibberella, and Tetracladium varied significantly between cropping patterns, and Leptosphaerulina was significantly associated with soil chemistry. Soil depth caused significant differences in the relative abundance of Fusarium in rotation and mixture soils, with Fusarium more commonly active at 0–15 cm deep soil. Null-model analysis revealed that the fungal community assembly of the mixture soils in 0–15cm deep soil was dominated by deterministic processes, unlike the other two cropping patterns. Furthermore, fungal symbiotic networks were more complex in rotation and mixture than in monoculture soils, reflected in more nodes, more module hubs, and connectors. The fungal networks in rotation and mixture soils were more stable than in monoculture soils, and mixture networks were obviously more connected than rotations. FUNGuild showed that the relative proportion of saprotroph in rotation and mixture was significantly higher than that in monocultures. The highest proportion of pathotroph and symbiotroph was exhibited in rotation and mixture soils, respectively. Overall, mixture is superior to crop rotation and monocultures in restoring fungal communities of the saline-alkali soils of the Western Songnen Plain, northeast China.